ANALYSIS OF SEDIMENT ORGANIC CONTENT AND MACROZOOBENTHOS ABUNDANCE IN THE WATERS OF SUNGAITOHOR VILLAGE KEPULAUAN MERANTI REGENCY RIAU PROVINCE - Anggraini Vista Yulandari; Bintal Amin; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in February - March 2019 in the waters of Sungaitohor Village Kepulauan Meranti Regency Riau Province. The aims of the study were to analyze the organic content in the sediment and macrozoobenthos abundance and the relationship of organic sediment with macrozoobenthos abundance. Determination of the research was purposive sampling of 4 station with 5 sampling points where the distance each sampling point was 500 meters wich were based on the initial sampling point. Makrozoobenthos in the study area consist of 10 species of 2 classes, namely class gastropod and malacostraca. The study showed that the organic content in the sediment was found between 8.57 – 26.07 %, while the abundance of macrozoobenthos was between 18.33 – 58.33 ind/m2. The relationship between macrozoobenthos and organic sediment was expressed with the equation of Y = 3.667 + 2.099X, r = 0.759, the higher content of organic sediment lead to the higher the makrozoobenthos abundance. Keywords: sediment organic, macrozoobenthos, abundance